Taxonomy for the technology domain - Tomei, Lawrence A. (Information Science Publishing, 2005)
"This book suggests a new classification system for classroom teaching that includes literacy, collaboration, decision-making, infusion, integration, and technology. As with most taxonomies, each step offers a progressively more sophisticated level of complexity by constructing increasingly multifaceted objectives addressing increasingly complex student learning outcomes. "--Provided by publisher.